BS ISO 11119-2. Gas cylinders. Refillable composite gas cylinders and tubes. Design, construction and testing. Part 2. Fully wrapped fibre reinforced composite gas cylinders and tubes up to 450 l with load-sharing metal liners (22nd August 2019) - British Standards Institution,
No abstract available